Assessment and quantification of meteorological data for implementation of weather radar in mountainous regions - KURIQI, ALBAN (MAUSAM, 2016)
The scope of this paper is to improve observation and detection of hydro-meteorological hazard over the Grenoble region which is characterised by significant changes of terrain in altitude and geomorphology. The city of Grenoble is located at a height between 200 up to 500 m, installing the weather radar in this range of elevation leads to better quality measurements, but visibility and as well coverage capability will be reduced at the other sites of the affected region. Two locations are shortlisted for the implementation of the future weather radar in Grenoble; (i) Moucherotte (1920 m a.s.l.) and (ii) Saint Eynard (1365 m a.s.l.). Several simulation and data analysis are performed to get the clear picture about precipitation variability by considering meteorological data from individual ground stations and radio sounding data as well. Compared to previous work, in this study is considered climatology of the vertical structure of the rainfall. In this context, several statistical computations are done regarding 0°C isotherm altitude. Concerning rainfall error estimation, ground clutter and screening effect, statistical calculations by using VISHYDRO code, are performed by for different quintiles for several elevation angles in both shortlisted sites. The results obtained from calculations carried out on two locations are almost similar. Also, significant under and over-estimation of rainfall error due to screening and ground clutter effect are detected. To achieve more accurate results, other sites need to be tested for further simulation. On the other hand since ground clutter, and screening effect at the Moucherotte is not too high compare with Saint Eynard, this site may be considered for implementing the future weather radar for observation of the meteorological processes over the Grenoble region.